The Amish Christmas letters - Davids, Patricia; Price, Sarah, 1969-; Beckstrand, Jennifer (Kensington Books, 2018)
To win a friendly annual competition, matchmaker Marybeth Martin must bring one more couple together by Christmas. Her only prospect is a man more interested in a nanny than a wife<U+2014>until his little girl shows him the light. . . . Struggling farmer<U+2019>s daughter Katie Mae Kauffman discovers that she and a local widower and father of four can harvest more crops<U+2014>and profits<U+2014>together than separately. But she<U+2019>ll have to put pride aside to make room for unexpected love. . . . Corralling an unruly brood of seven is not babysitter Carolyn Yutzy<U+2019>s first choice for celebrating the season<U+2014>but the sparks between her and their unsentimental yet irresistible uncle may be a gift neither was counting on . . . Now, one by one, each resourceful young woman will have a holiday to remember<U+2014>and to write home about . . .